Understanding and Preventing Violence, Volume 2: Biobehavioral Influences - National Research Council (The National Academies Press, 1994)
This volume contains commissioned reviews of research on biological influences on violent or aggressive behavior. The areas reviewed include genetic contributions to the probability of violent and related behaviors; brain structure and functioning as implicated in aggressive behavior; the roles of hormonal and neurological interactions in violent behavior; the neurochemistry of violence and aggression and its implications for the management of those behaviors; and dietary influences on violent behavior.

Flying in the COVID-19 Era: Science-based Risk Assessments and Mitigation Strategies on the Ground and in the Air: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on February 4th and 5th, 2021 to review the issues related to safety of passengers and employees in commercial air transportation, for domestic and international travel, during the COVID-19 pandemic. The workshop explored best practices to assess and mitigate COVID-19 transmission risks experienced during the travel chain, from the departure airport entrance to the destination airport exit. The workshop also identified areas where more research is needed to address gaps in understanding. This publication documents the presentations and discussions held during the workshop, and is presented as a synthesis of the workshop.

Scientific and Technological Cooperation Among Industrialized Countries: The Role of the United States (The National Academies Press, 1984)

Decadal Survey of Civil Aeronautics: Foundation for the Future - National Research Council (The National Academies Press, 2006)
The U.S. air transportation system is very important for our economic well-being and national security. The nation is also the global leader in civil and military aeronautics, a position that needs to be maintained to help assure a strong future for the domestic and international air transportation system. Strong action is needed, however, to ensure that leadership role continues. To that end, the Congress and NASA requested the NRC to undertake a decadal survey of civil aeronautics research and technology (R&T) priorities that would help NASA fulfill its responsibility to preserve U.S. leadership in aeronautics technology. This report presents a set of strategic objectives for the next decade of R&T. It provides a set of high-priority R&T challenges2014-characterized by five common themes2014-for both NASA and non-NASA researchers, and an analysis of key barriers that must be overcome to reach the strategic objectives. The report also notes the importance of synergies between civil aeronautics R&T objectives and those of national security.

Recent Trends in U.S. Aeronautics Research and Technology (The National Academies Press, 1999)

U.S.-European-Japanese Workshop on Space Cooperation: Summary Report (The National Academies Press, 1999)

Readiness for the Upcoming Solar Maximum (The National Academies Press, 1998)
Get your sunglasses on and get ready for the upcoming Solar Maximum.

Space Studies Board Annual Report 2008 (The National Academies Press, 2009)

Scientific Opportunities with a Rare-Isotope Facility in the United States - National Research Council (The National Academies Press, 2007)
Over ten years ago, U.S. nuclear scientists proposed construction of a new rare isotope accelerator in the United States, which would enable experiments to elucidate the important questions in nuclear physics. To help assess this proposal, DOE and NSF asked the NRC to define the science agenda for a next-generation U.S. Facility for Rare Isotope Beams (FRIB). As the study began, DOE announced a substantial reduction in the scope of this facility and put off its initial operation date by several years. The study focused on an evaluation of the science that could be accomplished on a facility reduced in scope. This report provides a discussion of the key science drivers for a FRIB, an assessment of existing domestic and international rare isotope beams, an assessment of the current U.S. position about the FRIB, and a set of findings and conclusions about the scientific and policy context for such a facility.

NASA'S Role in Aeronautics: A Workshop - National Research Council (The National Academies Press, 1981)

Report on Human Response to the Sonic Boom - National Research Council (The National Academies Press, 1968)

Advanced Organic Composite Materials for Aircraft Structures: Future Program - National Research Council (The National Academies Press, 1987)

Approaches to Future Space Cooperation and Competition in a Globalizing World: Summary of a Workshop - National Research Council
Numerous countries and regions now have very active space programs, and the number is increasing. These maturing capabilities around the world create a plethora of potential partners for cooperative space endeavors, while at the same time heightening competitiveness in the international space arena. This book summarizes a public workshop held in November 2008 for the purpose of reviewing past and present cooperation, coordination, and competition mechanisms for space and Earth science research and space exploration; identifying significant lessons learned; and discussing how those lessons could best be applied in the future, particularly in the areas of cooperation and collaboration. Presentations and initial discussion focused on past and present experiences in international cooperation and competition to identify \

Foundations of a Healthy and Vital Research Community for NASA Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The U.S. space science community includes thousands of scientists across multiple disciplines that influence and are influenced by the many engineers, technicians, and support personnel that are part of the space research enterprise. Over one-third of NASA's budget is devoted to space science, and the agency currently operates over 50 space missions in the fields of astrophysics, Earth science, solar and space physics, planetary science, and the biological and physical sciences. The strength of NASA science lies with its people, both those who work directly for the agency and the thousands of researchers and professionals who are funded by NASA grants and contracts. At the request of NASA, this report examines the foundation for healthy and vital research communities. Foundations of a Healthy and Vital Research Community for NASA Science identifies the characteristics of a healthy and vital research community, defines implementable measures for assessing the health and vitality of a research community, describes the types of data that NASA should be collecting to enable future assessments of the health and vitality of the scientific work force, and recommends best practices to improve the health and vitality of NASA2019s research communities.

Issues and Opportunities Regarding the U.S. Space Program: A Summary Report of a Workshop on National Space Policy - National Research Council (The National Academies Press, 2004)
Ever since the completion of the Apollo program, there has been a lack of consensus about the future of human spaceflight. The Columbia tragedy in February 2003 rekindled public debate about this question. In November 2003, the Space Studies Board and the Aeronautics and Space Engineering Board organized a workshop to explore aspects of the question, what should be the principal purpose, goals, and priorities of the U.S. civil space program? This report presents a factual summary of that workshop, which identified past lessons learned and guiding principles for the future of the civil space program. Seven broad themes emerged from the workshop, and these themes are highlighted in the report. The report also presents discussions of strategies for the human spaceflight program and guiding principles of and boundary conditions for a 21st century space policy.

Radioisotope Power Systems: An Imperative for Maintaining U.S. Leadership in Space Exploration - National Research Council (The National Academies Press, 2009)
Spacecraft require electrical energy. This energy must be available in the outer reaches of the solar system where sunlight is very faint. It must be available through lunar nights that last for 14 days, through long periods of dark and cold at the higher latitudes on Mars, and in high-radiation fields such as those around Jupiter. Radioisotope power systems (RPSs) are the only available power source that can operate unconstrained in these environments for the long periods of time needed to accomplish many missions, and plutonium-238 (238Pu) is the only practical isotope for fueling them. Plutonium-238 does not occur in nature. The committee does not believe that there is any additional 238Pu (or any operational 238Pu production facilities) available anywhere in the world.The total amount of 238Pu available for NASA is fixed, and essentially all of it is already dedicated to support several pending missions–the Mars Science Laboratory, Discovery 12, the Outer Planets Flagship 1 (OPF 1), and (perhaps) a small number of additional missions with a very small demand for 238Pu. If the status quo persists, the United States will not be able to provide RPSs for any subsequent missions.

Aviation After a Year of Pandemic: Economics, People, and Technology: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Among the various segments of society affected by the COVID-19 pandemic over the past year and a half, few were hit as hard as the aviation industry. At its worst point, in March 2020, passenger volumes for U.S. airlines had dropped more than 95 percent. Airlines, airports, aircraft manufacturers, and other components of the air travel system faced an unprecedented challenge, with threats to the health of passengers and crews combined with threats to the financial health of the entire system. To address the many COVID-related issues facing the aviation industry, on June 28-30, 2021, the Aeronautics and Space Engineering Board of the National Academies of Sciences, Engineering, and Medicine hosted a three-day workshop, Aviation After a Year of Pandemic - Economics, People, and Technology. Funded by the National Aeronautical and Space Administration and held remotely via Zoom, the workshop focused on four specific areas regarding the effects of COVID on the aviation industry: economics, personnel, technology, and next steps. This publication summarizes the presentation and discussion of the workshop.

NASA's Strategic Direction and the Need for a National Consensus - National Research Council
The National Aeronautics and Space Administration (NASA) is widely admired for astonishing accomplishments since its formation in 1958. Looking ahead over a comparable period of time, what can the nation and the world expect of NASA? What will be the agency's goals and objectives, and what will be the strategy for achieving them? More fundamentally, how will the goals, objectives, and strategy be established and by whom? How will they be modified to reflect changes in science, technology, national priorities, and available resources? In late 2011, the United States Congress directed the NASA Office of Inspector General to commission a \

Advancing Aerial Mobility: A National Blueprint - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Advanced aerial mobility is a newly emerging industry that aims to develop and operate new air vehicles potentially capable of safe, reliable, and low-noise vertical flight. The world has seen a recent increase in the adoption of electric vertical lift aircraft for urban, suburban and rural operations. These new innovations and technologies change the way that we move cargo and people, affecting industries across the economy. These changes will challenge today's airspace monitoring systems and regulatory environment. The U.S. government and its regulatory agencies need technical guidance to facilitate the development of these technologies, and to create the regulatory framework to foster the growth of this vertical flight industry to the benefit of the aviation industry. Advancing Aerial Mobility evaluates the potential benefits and challenges associated with this emerging industry. This report provides recommendations that seek to foster an environment in which the nation can maintain its leading position in developing, deploying, and embracing these new technologies. This publication presents a national vision for advanced aerial mobility, market evolution, and safety and security management.

Aeronautics Innovation: NASA's Challenges and Opportunities - National Research Council (The National Academies Press, 2006)
NASA is a global leader in aeronautics research and development 2014 fostering advances in aviation safety and emissions, propulsion technology, and many other areas. And the agency's Aeronautics Research Mission Directorate (ARMD) has played a vital role in the U.S. aeronautics industry. In recent years, the directorate's leaders and experts outside the agency have sought ways to speed innovative uses of ARMD's research results. But the directorate faces management challenges that make it difficult for such applications to succeed 2014 or to occur at all. This report from the National Academies' National Research Council, offers the agency guidance on how to manage the transfer of technology to external users, as well as implement flexible personnel and financial-management practices. The report also points out problems that stem from a lack of agreement on ARMD's future direction and several years of federal budget cuts.